Mixed convection in laminar film flow of a micropolar fluid - Ahmad, Kartini; Nazar, Roslinda; Pop, Loan (Pergamon-Elsevier Science Ltd, 2012)
In this paper, the steady mixed convection boundary layer in laminar film flow of a micropolar fluid is considered. The resulting nonlinear coupled ordinary differential equations are solved numerically using an efficient implicit finite-difference scheme. The numerical results obtained for the skin friction coefficient and the local Nusselt number, as well as the velocity, angular velocity or microrotation and temperature profiles are presented in tables and figures for different values of the material parameter K and the Richardson number Ri when the Prandtl number Pr= 0.7 and Pr= 1.